Sleep Deprivation Disrupts Acquisition of Contextual Fear Extinction by Affecting Circadian Oscillation of Hippocampal-Infralimbic proBDNF - Sun, Wei (eNeuro, 2019)
Extensive evidence showed that mature brain-derived neurotrophic factor (mBDNF) levels displayed a circadian pattern. Circadian disruption, for example, sleep deprivation (SD), induced functional and behavioral deficits. However, compared with that of mature form, the biological role of the pro-peptide, proBDNF, was poorly understood. Here, we found that proBDNF was expressed under circadian rhythm in the ventral hippocampus (vHPC). SD rats exhibited deficits in acquisition of conditioned extinction and damped rhythmicity in vHPC proBDNF activity that were accompanied by SD between zeitgeber time (ZT)0 and ZT4, but not the late stage of sleep period. Furthermore, SD affected fear extinction through vHPC-IL proBDNF signaling, which was associated with NR2B subunits of NMDA receptors. More importantly, infusion of proBDNF could mitigate SD-induced abnormal neural activity, by suppressing the enhanced basal firing rate of IL-RS and elevating the depressed neural response that evoked by acquisition of conditioned extinction. Therefore, this finding provided the first evidence that circadian oscillation of vHPC proBDNF activity contributed to the effects of SD on acquisition of conditioned fear extinction, and suggested a new therapeutic target to reverse the cognitive deficits in sleep-related mental disorder, such as post-traumatic stress disorder (PTSD).